(untitled) (Journal of Computational Mathematics, 2001)
This paper present a way to construct orthogonal piece-wise polynomials on an arbitrary triangular domain via barycentric coordinates. A boundary value problem for Laplace equation and its eigenvalue problem can be solved as two applications of this approach.